A critical review on earthquake resistant design provisions of SNI 03-1726-2002 of Indonesia and IS 1893 (part 1)-2002 of India - Ngeljaratan, Luna; Kamatchi, P.; Iyer, Nagesh R. (Journal of Structural Engineering, 2024)
This paper presents a critical review of earthquake resistant design provisions in seismic codes of Indonesia and India. Being located at the neighborhood landmass of active Indian Ocean, seismological background and the extent of damage experienced in past large earthquakes in terms of human casualities necessitates the review of the existing earthquake resistant design provisions of both the countries with reference to current international codes. The similarities and differences in both the codes with reference to International building code in terms of risk level specifi cation, seismic zone map, response spectra, soil classifi cation, importance factor, ductility factors, provisions for irregularity, time period determination, analyses types for base shear estimation and performance criteria are discussed. The study has brought out the salient features which are overlooked in both the codes and the scope for further improvement is suggested.